2018
DOI: 10.1007/s10661-018-7051-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of cadmium, lead, and zinc in agriculture-based insect food chains

Abstract: Globally, the metals concentration in soil is increasing due to different anthropogenic and geogenic factors.These metals are taken up by plants and further transferred in the food chain through different routes. The present study was designed to assess the transfer and bioaccumulation of the heavy metals, cadmium (Cd), lead (Pb) and zinc (Zn), in food chains from soil to berseem plants (Triofolium alexandrinum), to insect herbivores (the grasshopper Ailopus thalassinus and the aphid Sitobion avenae) and to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 69 publications
(77 reference statements)
1
29
1
1
Order By: Relevance
“…The BI values differed significantly for metals. Butt et al (2018) reported that they recorded the highest average bio-accumulation factor (BAF) for Zn (3.35) and the least for Cd (1.22) with intermediate values for Pb (2.94). The higher values are adopted by BI, the higher concentration of the element is determined in the plant biomass in reference to the initial values in soil.…”
Section: Bio-accumulation Indicesmentioning
confidence: 99%
“…The BI values differed significantly for metals. Butt et al (2018) reported that they recorded the highest average bio-accumulation factor (BAF) for Zn (3.35) and the least for Cd (1.22) with intermediate values for Pb (2.94). The higher values are adopted by BI, the higher concentration of the element is determined in the plant biomass in reference to the initial values in soil.…”
Section: Bio-accumulation Indicesmentioning
confidence: 99%
“…Some studies traditionally focus on the evaluation of the accumulation in insects [ 43 ], while other works emphasize insects as bioindicators of environmental pollution [ 1 ]. Recently, there is an increased effort in research focused on the transfer of different heavy metals via the whole terrestrial [ 44 , 45 ] and aquatic [ 46 , 47 ] food chains (including insects). The effects of certain heavy metal on fitness traits of insect species have been studied sporadically [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are known as naturally occurring compounds, but the anthropogenic activities enhance their distribution in the environment. Undesirable human activity leads to their bioaccumulation in the food chains .…”
Section: Introductionmentioning
confidence: 99%